Peningkatan Kapasitas Sumber Daya Manusia melalui Pelatihan Pemasaran Digital Di UMKM Wayang Uwuh Yogyakarta: Peningkatan Kapasitas Sumber Daya Manusia melalui Pelatihan Pemasaran Digital Di UMKM Wayang Uwuh Yogyakarta - Agustina, Granit; Nalibratawati, Rakhmia; Romli; Febrian, Febi; Adiyanti, Siska Ayudia (LPPM UKRI, 2026)
Wayang Uwuh Yogyakarta MSME is a creative business that transforms waste into art while campaigning for environmental awareness. However, the partner faces challenges regarding limited human resources skilled in digital marketing. The goal of this community service is to increase HR capacity through digital marketing training to enhance competitiveness and income. The method includes needs identification through surveys and interviews, material design, training implementation (presentations, discussions, hands-on practice), evaluation, and mentoring. Results show significant improvements in participants' knowledge (80%), technical skills (70%), and confidence in digital business (90%). Nevertheless, challenges such as time and resource constraints remain concerns for future mentoring programs.